Fighting Alone: The Lived Experiences of African Women Immigrant Farmers Acquiring Land in the U.S. - Willis Ochieng; Damilola Ajayi (Journal of International Agricultural and Extension Education, 2023)
The study adopted phenomenology to understand the lived experiences of African Women Immigrant Farmers (AWIFS) acquiring land in the U.S. Seven participants were interviewed through semi-structured interviews. The study found that AWIFs acquire land from friends, and organizations serving immigrants, including government agencies. AWIFS also partners with spouses or close relatives to purchase agricultural land. Nonetheless, AWIFS experiences numerous challenges such as limited social networks which restrict access to land-related information. Other challenges include a lack of knowledge of American land structures and tenure systems, financial challenges, and stringent funding requirements. To overcome such barriers, AWIFS, engage in expanding their social networks and research to acquire land-related information. The study recommends that organizations supporting immigrant farmers focus on building close relationships with immigrant farmers as a springboard to effectively address their unique needs. Additionally, organizations serving immigrant farmers should provide a bundle of services including capital, land, extension services, and market infrastructures to alleviate financial stress and unlock AWIFS’ full potential.
Keywords: Africa; Challenges; Immigrant farmers; Land Access; Women Farmers.